Contribution of Internalization of Religious Values to Strengthening Childhood Character: Systematic Literature Review in The Framework of Sustainable Development and Inclusive Peace - Luthfatun Nisa'; Ma’arif, Moh. Samsul (IAIN Madura, 2025)
This study aims to analyze the internalization of religious values ​​in the development of early childhood character and its relation to SDG 4.7 (education for sustainable development) and SDG 16 (inclusive peace and justice). Internalization of religious values ​​is an important foundation for building children's spiritual attitudes through the habit of worship such as prayer, dhikr, and polite behavior. This study uses the Systematic Literature Review (SLR) method to systematically identify, evaluate, and interpret relevant literature based on predetermined provisions and limitations. The literature used is limited to the internalization of religious values ​​in the Pamekasan Community. The results of the study show that in Pamekasan, the internalization of religious values ​​is carried out through a synergistic approach to family, educational institutions, and community communities. This process forms the spiritual attitudes of early childhood which are reflected in the practice of worship and civilized social behavior. Internalization of religious values ​​also plays a role in strengthening children's character as part of inclusive and sustainable education, in accordance with the goals of SDG 4.7 and SDG 16. These findings show the importance of cross-sector collaboration in forming a generation that is religious, peace-loving, and just from an early age.